All Days 2013
DOI: 10.2118/167023-ms
|View full text |Cite
|
Sign up to set email alerts
|

Post-Shutdown Recovery Behavior of Horizontal Coalbed Methane Wells in the Bowen Basin

Abstract: A number of coalbed methane (CBM) to liquefied natural gas (LNG) projects are currently advancing in Australia, among which is the Arrow LNG project. To ensure reliable supply to an LNG plant, production availability of the integrated CBM system consisting of a large amount of wells and production facilities needs to be understood, including the behavior of CBM wells after planned and unplanned shutdowns. This paper provides an analysis of post-shutdown recovery behavior of horizontal CBM wells based on a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The peak gas rates of the individual wells varied from 253 to 48819 m 3 /d with a mean of 9840 m 3 /d. This wide variation in productions is due to the coal reservoir properties and engineering factors. …”
Section: Geologic Settings Data and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The peak gas rates of the individual wells varied from 253 to 48819 m 3 /d with a mean of 9840 m 3 /d. This wide variation in productions is due to the coal reservoir properties and engineering factors. …”
Section: Geologic Settings Data and Methodologymentioning
confidence: 99%
“…Since the engineering factors have significant impacts on the gas production, , the production behavior of each well should be analyzed before conducting the history matching for the individual wells. It was found that most low producers used open annulus and gravel-packed completion types, and the abnormal low production at a particular period was usually affected by the unreasonable drainage working systems, such as a sudden decrease in BHFP and noncontinuous dewatering.…”
Section: History Matching Processmentioning
confidence: 99%
“…CBM wells are also prone to unplanned shutdowns (Gilbert, et al, 2013) resulting in discontinuities in the production profile.…”
Section: Unconventional Gas Reservoir Uncertaintymentioning
confidence: 99%
“…4 Adding irregularities to synthetic type curves Unconventional gas wells do not follow a smooth type curve partly due to being subject to planned and unplanned shut-ins (Gilbert et al 2013 as noise or irregular flow deviations from a smooth production curve is likely not actual gas production from the well, but rather external influences on the measurement such as flow meter failure or maintenance work interrupting either production or control system functionality. The causes for the noise in data can be anything, and likely to be external and not representative of a reservoir's actual performance.…”
mentioning
confidence: 99%